2017
DOI: 10.3389/fvets.2017.00097
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Nasal Colonization Differs among Pig Lineages and Is Associated with the Presence of Other Staphylococcal Species

Abstract: Staphylococcus aureus is a common colonizer in pigs, with methicillin-resistant S. aureus (MRSA) in particular being a potential health risk to humans. To reduce the exposure to humans, the colonization in pigs should be reduced. The aim of this study was to quantitatively compare the susceptibility of pig lineages for S. aureus colonization, and if the absence of S. aureus could be associated with the presence or absence of other staphylococcal species. Nasal samples (n = 129) were obtained from seven differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
18
2
Order By: Relevance
“…In our investigation we also found S. sciuri to be the most prevalent CoNS being isolated from 40% of the pigs followed by S. lentus and S. xylosus. Unlike the Verstappen study though, we did not isolate S. saprophyticus or S. cohnii which were the other most prominent species identified along with S. sciuri (Verstappen et al, 2017).…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…In our investigation we also found S. sciuri to be the most prevalent CoNS being isolated from 40% of the pigs followed by S. lentus and S. xylosus. Unlike the Verstappen study though, we did not isolate S. saprophyticus or S. cohnii which were the other most prominent species identified along with S. sciuri (Verstappen et al, 2017).…”
Section: Discussioncontrasting
confidence: 61%
“…Likewise, pigs have been reported to be colonized by a variety of CoNS with one study describing 10 species including S. hyicus , Staphylococcus haemolyticus , Staphylococcus warneri , S. simulans , S. xylosus , and S. sciuri to be isolated at approximately equal frequency (Nagase et al, 2002). Others document higher CoNS species numbers (between 18 and 20 different CoNS) including the afore-mentioned, as well as S. saprophyticus and S. cohnii (Schoenfelder et al, 2017; Verstappen et al, 2017). However, both the latter studies report a marked increase in S. sciuri prevalence over the other species amounting to between 30 and 46% of the total colonizing CoNS species (Schoenfelder et al, 2017; Verstappen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. hominis and S. capitis proportional abundances were not associated with either AD disease or disease exacerbation in children [ 4 , 19 ], however, these studies included less than 12 volunteers, which limits their ability to detect such associations. The importance of S. cohnii for human skin health is not clear, but one study has shown a negative correlation between S. aureus and S. cohnii colonization of the nasal epithelium in pigs [ 55 ]. This may indicate an antagonistic interaction between S. aureus and S. cohnii .…”
Section: Discussionmentioning
confidence: 99%